Memristive TiO2: Synthesis, Technologies, and Applications - Illarionov, Georgii A.; Morozova, Sofia M.; Chrishtop, Vladimir V.; Einarsrud, Mari-Ann; Morozov, Maxim I. (Frontiers in Chemistry, 2020)
Titanium dioxide (TiO2) is one of the most widely used materials in resistive switching applications, including random-access memory, neuromorphic computing, biohybrid interfaces, and sensors. Most of these applications are still at an early stage of development, meet technological challenges and lack of fundamental comprehension. Furthermore, the functional memristive properties of titanium dioxide thin films are drastically dependent on their processing methods, including synthesis, fabrication, and post-fabrication treatment. Here, we outline and summarize the key milestone achievements, recent advances and challenges related to synthesis, technologies, and applications of memristive titanium dioxide. Following a brief introduction, we provide an overview of the major application domains of TiO2-based memristive devices and discuss their relations to synthesis, fabrication, and post-fabrication processing, as well as functional properties.